STRATEGI PEMASARAN KEDELAI DI KOTA MANOKWARI SOYBEAN MARKETING STRATEGY IN THE MANOKWARI CITY - Kurniawan, Anang; Abdullah, Yunus; Simanungkalit, Saut (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2014)
This study was conducted to determine determine the marketing strategies used by employers soybean imports in the city of Manokwari. There are also other things to be extracted is the price of soybeans at the time of purchase, how employers promote soybean and to determine the total volume of imported soybeans. This research was conducted in the district of Manokwari start of December 6, 2013 to February 7, 2014. Methods used descriptive case study technique. These results indicate that the marketing strategies used by both companies this is a strategy in which the price when buying in large quantities of consumer got a discounted price. Other results obtained in this study are from year to year soybean prices have increased in line with the relative price of the dollar. There is also the price at time of purchase in the amount of Rp. 8,000 per kg, the importer sold it for Rp. 9,000 per Kg way companies promote their goodsare not too complicated simply put a banner in front of his shop and or private radio. Famous for its business customers tell langgananya that other consumers. Soybeans are sold in a single transaction, could serve 99% of the volume of soybean imports.